2020
DOI: 10.1016/j.jid.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Epidermal Differentiation, Aging, and Cancer

Abstract: The formation and maintenance of the epidermis depend on epidermal stem cell differentiation and must be tightly regulated. Epigenetic mechanisms such as DNA methylation allow the precise gene expression cascade needed during cellular differentiation. However, these mechanisms become deregulated during aging and tumorigenesis, where cellular function and identity become compromised. Here we provide a review of this rapidly developing field. We discuss recent discoveries related to epidermal homeostasis, aging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 136 publications
1
51
0
1
Order By: Relevance
“…Most of the genes had low methylation levels. Aberrant DNA methylation plays a crucial role in carcinogenesis [25, 26]. Therefore, we speculate that hypomethylation may be one cause of the upregulation of the 20 hub genes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the genes had low methylation levels. Aberrant DNA methylation plays a crucial role in carcinogenesis [25, 26]. Therefore, we speculate that hypomethylation may be one cause of the upregulation of the 20 hub genes.…”
Section: Discussionmentioning
confidence: 99%
“…Global DNA hypomethylation and differential promoter methylation are major characteristics of tumorigenesis. Global hypomethylation of the entire genome in peripheral blood leukocytes is demonstrated as the risk factor for colorectal and breast cancer [[10], [11], [12], [13]]. DNA hypomethylation on the promoter region was linked to increased expression of cyclin D2 and maspin in gastric carcinoma and elevated carbonic anhydrase family gene in human renal-cell carcinoma [[14], [15], [16]].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that altered circadian regulation in cancer stem cells may contribute to disease progression (9). Endogenous circadian rhythms are maintained by two feedback loops.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous circadian rhythms are maintained by two feedback loops. Clock circadian regulator (CLOCK) and brain and muscle Arnt-like protein-1 (BMAL1) form heterodimers to rhythmically activate the expression of transcriptional repressor proteins, such as period 1/2/3 and cryptochrome 1/2, which form a complex to inhibit CLOCK and BMAL1 transcriptional activity (9)(10)(11). In some types of cancer and model systems, period circadian clock 2 (PER2) serves as a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%